2022
DOI: 10.1021/acscatal.2c03876
|View full text |Cite
|
Sign up to set email alerts
|

Site-Selective Modification of (Oligo)Saccharides

Abstract: Oligosaccharides, either as such or as part of glycolipids, glycopeptides, or glycoproteins, are ubiquitous in nature and fulfill important roles in the living cell. Also in medicine and to some extent in materials, oligosaccharides play an important role. In order to study their function, modifying naturally occurring oligosaccharides, and building in reactive groups and reporter groups in oligosaccharides, are key strategies. The development of oligosaccharides as drugs, or vaccines, requires the introductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 81 publications
(112 reference statements)
0
11
0
Order By: Relevance
“…In conclusion, we have demonstrated the employment of chiral Rh(I) catalysis synergistically with boronic acid catalysis in site-selective carbohydrate functionalizations, 81 surmounting the challenge of multiple regio-, diastereo-, enantio- and anomeric control within a single bond-forming step. Thus, this method paves the way for stereoselective access into biologically relevant arylnaphthalene glycosides.…”
Section: Discussionmentioning
confidence: 95%
“…In conclusion, we have demonstrated the employment of chiral Rh(I) catalysis synergistically with boronic acid catalysis in site-selective carbohydrate functionalizations, 81 surmounting the challenge of multiple regio-, diastereo-, enantio- and anomeric control within a single bond-forming step. Thus, this method paves the way for stereoselective access into biologically relevant arylnaphthalene glycosides.…”
Section: Discussionmentioning
confidence: 95%
“…The reported studies in which the quinuclidinium radical cation has been used to achieve HAT from sugars reveal general trends regarding site selectivity. Formation of a radical at C3 of α-gluco-configured pyranosides is a particularly prevalent outcome, as evidenced by the efficient reactivity of such substrates in photoredox/HAT co-catalyzed C–H alkylations, OH group epimerizations, and redox isomerizations. Upon changing the anomeric configuration from α to β, the yields for the same transformations have been found to drop markedly (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, protecting group strategies are used to implement the desired modifications [21,22] . As an alternative to the commonly used strategies, the field of regioselective modification of unprotected carbohydrates is growing rapidly [23–25] . In this connection, the groups of Minnaard and Waymouth have shown that the C‐3 hydroxy group in pyranosides can be selectively oxidized with a palladium catalyst to afford the corresponding 3‐ketosaccharide [26–29] .…”
Section: Introductionmentioning
confidence: 99%